Impact on emergency and elective hospital-based care in Scotland over the first 12 months of the pandemic: interrupted time-series analysis of national lockdowns. (November 2022) - Shah, Syed Ahmar; Mulholland, Rachel H; Wilkinson, Samantha; Katikireddi, Srinivasa Vittal; Pan, Jiafeng; Shi, Ting; Kerr, Steven; Agrawal, Uktarsh; Rudan, Igor; Simpson, Colin R; Stock, Sarah J; Macleod, John; et al.
Objectives: COVID-19 has resulted in the greatest disruption to National Health Service (NHS) care in its over 70-year history. Building on our previous work, we assessed the ongoing impact of pandemic-related disruption on provision of emergency and elective hospital-based care across Scotland over the first year of the pandemic. Design: We undertook interrupted time-series analyses to evaluate the impact of ongoing pandemic-related disruption on hospital NHS care provision at national level and across demographics and clinical specialties spanning the period 29 March 2020–28 March 2021. Setting: Scotland, UK. Participants: Patients receiving hospital care from NHS Scotland. Main outcome measures: We used the percentage change of accident and emergency attendances, and emergency and planned hospital admissions during the pandemic compared to the average admission rate for equivalent weeks in 2018–2019. Results: As restrictions were gradually lifted in Scotland after the first lockdown, hospital-based admissions increased approaching pre-pandemic levels. Subsequent tightening of restrictions in September 2020 were associated with a change in slope of relative weekly admissions rate: –1.98% (–2.38, –1.58) in accident and emergency attendance, –1.36% (–1.68, –1.04) in emergency admissions and –2.31% (–2.95, –1.66) in planned admissions. A similar pattern was seen across sex, socioeconomic status and most age groups, except children (0–14 years) where accident and emergency attendance, and emergency admissions were persistently low over the study period. Conclusions: We found substantial disruption to urgent and planned inpatient healthcare provision in hospitals across NHS Scotland. There is the need for urgent policy responses to address continuing unmet health needs and to ensure resilience in the context of future pandemics.